Prospective performance of the Prostate Health Index in prostate cancer detection in the first prostate biopsy of men with a total prostatic specific antigen of 4–10 ng/mL and negative digital rectal examination - Supon Sriplakich (2018)
© 2018 Background: The disadvantage of using total serum prostatic specific antigen (PSA) test for detection of prostate cancer is that it has a low specificity. The low specificity of total PSA (tPSA) test leads to unnecessary prostate biopsies. In this prospective study, we assessed the serum tPSA, free PSA, p2PSA, and the Prostate Health Index (PHI) in the detection of prostate cancer in men with a tPSA of 4–10 ng/mL and a negative digital rectal examination (DRE). Materials and methods: 101 male outpatients with a serum PSA of 4–10 ng/mL and nonsuspicious DRE for prostate cancer who underwent first transrectal ultrasound with a prostate biopsy were recruited. A blood sample to enable tPSA, free PSA, and p2PSA levels to be calculated was drawn before the prostate biopsy. The diagnosis and detection of high-grade cancer are correlated with the blood sample. Results: Sixteen patients were positive for prostate cancer. All had significantly higher serum 2pPSA and PHI levels than patients with no cancer. A PHI level at 90% sensitivity (cutoff of 34.14) demonstrated a higher area under the receiver operating characteristic curve and more specificity in diagnosis and detection of high-grade prostate cancer than other tests. Conclusions: The PHI in men with a PSA level of 4–10 ng/mL with negative DRE increased specificity in the detection of prostate cancer. This test is useful in discriminating between patients with or without cancer and also enables the detection of high-grade cancer avoiding unnecessary biopsies.